Terahertz Science and Technology in Astronomy, Telecommunications, and Biophysics - Jing Li; Xianjin Deng; Yangmei Li; Jie Hu; Wei Miao; Changxing Lin; Jun Jiang; Shengcai Shi (Research)
This paper reviews recent developments and key advances in terahertz (THz) science, technology, and applications, focusing on 3 core areas: astronomy, telecommunications, and biophysics. In THz astronomy, it highlights major discoveries and ongoing projects, emphasizing the role of advanced superconducting technologies, including superconductor–insulator–superconductor (SIS) mixers, hot electron boundedness spectroscopy (HEB), transition-edge sensors (TESs), and kinetic inductance detectors (KIDs), while exploring prospects in the field. For THz telecommunication, it discusses progress in solid-state sources, new communication technologies operating within the THz band, and diverse modulation methods that enhance transmission capabilities. In THz biophysics, the focus shifts to the physical modulation of THz waves and their impact across biological systems, from whole organisms to cellular and molecular levels, emphasizing nonthermal effects and fundamental mechanisms. This review concludes with an analysis of the challenges and perspectives shaping the future of THz technology.